Correlation of optical energy onto nano-Additivated CuS/PA12 and LaB6/PA12 powder with depth of fusion in PBF-LB/P - Leupold, Simon; Willeke, Michael; Leong, Cheechau; Stratmann, Nadine; Sommereyns, Alexander; Ziefub, Anna Rosa; Kopp, Sebastian-Paul; Barcikowski, Stephan; Schmidt, Michael (Procedia CIRP, 2024)
The printability in laser powder bed fusion of polymers is significantly depended on the absorption of the laser light and the energy density provided by the laser. Most commonly, a CO2 laser is used for PBF-LB/P requiring no additional absorbers. However, when utilizing near-infrared diode lasers, additional absorbers are needed as the polymers themselves do not absorb enough energy at this wavelength. The interactions of light, polymer and absorbers have yet to be fully understood. In this study, the absorptance and resulting geometry of polyamide 12 coated with CuS and LaB6 nanoparticles, made by high-power laser-fragmentation, were analyzed. Multilayer samples consisting of five layers were manufactured at specific energy densities, using a 808 nm PBF-LB/P diode laser setup, and the resulting dimensions were measured. The results suggest that the nanoparticle intrinsic properties can significantly affect resulting geometrical accuracy, even for small quantities of nanoparticles.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Copper monosulfide nanoparticles; Lanthanum hexaboride nanoparticles; NIR Laser; PA12; PBF-LB/P